Electrochemical Characteristics of Capacitor Systems Formed on Chemical Modified Carbon Basis - Ostafiychuk, B.K.; Budzulyak, I.M.; Mandzyuk, V.I.; Lisovskyy, R.P. (Наносистеми, наноматеріали, нанотехнології, 2009)
Influence of chemical modification of an activated carbon (AC) material on its specific capacity is studied using methods of impedance spectroscopy, cyclic voltammetry and chronopotentiometry. As shown, the total capacity is the sum of two components–double electric layer (DEL) capacity and pseudocapacity; the contribution of the latter is insignificant (8—14%). The alloying with rareearth metals and their compounds results in the rise of specific capacity of AC. Probably, the principal cause of such a growth is transformation of valence band of carbon material caused by introduction of additional electron states from the introduced metals. As a result, considerably greater number of ions (especially, positive ones) will take part in DEL forming and, consequently, predetermine growth of specific capacity.